2019
DOI: 10.1136/jnnp-2019-anzan.23
|View full text |Cite
|
Sign up to set email alerts
|

024 Resistance exercises with blood flow restriction in patients with sporadic inclusion body myositis

Abstract: IntroductionSporadic inclusion body myositis (sIBM) is the most common muscle disease affecting older adults with no disease-modifying treatment. Resistance exercises increase muscle hypertrophy, but weakness prevents exercising with higher resistance. In healthy subjects, augmentation of light-load training with blood flow restriction improved muscle strength1; and similar exercises were safe in the elderly.2 We therefore investigate whether resistance exercises with blood flow restriction is safe and helpful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Both groups examined similar variables in their patientsdquality of life, strength, self-reported function, and endurance. Liang et al 103 found favorable results for the BFR group in all variables. Jørgensen et al 104 did not note significant differences in selfreported or objective outcomes, but they did find that the BFR group did not encounter diminished strength versus the controls.…”
Section: Neurologic/systemic Disordersmentioning
confidence: 95%
See 1 more Smart Citation
“…Both groups examined similar variables in their patientsdquality of life, strength, self-reported function, and endurance. Liang et al 103 found favorable results for the BFR group in all variables. Jørgensen et al 104 did not note significant differences in selfreported or objective outcomes, but they did find that the BFR group did not encounter diminished strength versus the controls.…”
Section: Neurologic/systemic Disordersmentioning
confidence: 95%
“…Some notable studies have already set the groundwork for the use of BFR in patient populations outside of the orthopedic and sports realms. Liang et al 103 and Jørgensen et al 104 have performed similar randomized control trials in patient populations with sporadic inclusion-body myositis. Both groups examined similar variables in their patientsdquality of life, strength, self-reported function, and endurance.…”
Section: Neurologic/systemic Disordersmentioning
confidence: 97%